2000
DOI: 10.1097/00001756-200006260-00022
|View full text |Cite
|
Sign up to set email alerts
|

Activity-induced plasticity in brain stem pain modulatory circuitry after inflammation

Abstract: Brain stem descending pathways modulate spinal nociceptive transmission. In a lightly anesthetized rat preparation, we present evidence that such descending modulation undergoes time-dependent changes following persistent hindpaw inflammation. There was an initial decrease and a subsequent increase in the excitability of neurons in the rostral ventromedial medulla (RVM) involving facilitation and inhibition. These changes were most robust after stimulation of the inflamed paw although similar findings were see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 11 publications
8
59
0
1
Order By: Relevance
“…Similar views have been advanced to account for the loss of spinal morphine suppression of somatic nociception and tactile allodynia following tight ligation of L5/L6 nerves. 24 There also is abundant evidence that descending inhibitory systems derived from either the rostroventral medulla (RVM) 11,32 or the locus coeruleus (LC) [33][34][35][36] are recruited following inflammation of somatic tissue. While these descending systems are present at birth, they are only partially functional by P10-P12 and become functionally mature by P21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar views have been advanced to account for the loss of spinal morphine suppression of somatic nociception and tactile allodynia following tight ligation of L5/L6 nerves. 24 There also is abundant evidence that descending inhibitory systems derived from either the rostroventral medulla (RVM) 11,32 or the locus coeruleus (LC) [33][34][35][36] are recruited following inflammation of somatic tissue. While these descending systems are present at birth, they are only partially functional by P10-P12 and become functionally mature by P21.…”
Section: Discussionmentioning
confidence: 99%
“…26 This enhanced bladder response was paralleled by a more global bladder hypersensitivity, manifested as increased micturition frequency 26 and decreased thresholds for micturition reflexes during cystometry. 8 Other studies of primary hyperalgesia and inflammation involving either the knee joint 31 or the hindpaw 28,39 have shown that descending inhibitory systems are progressively engaged during the first 24 hrs of acute inflammation and act to suppress somatic hyperalgesia (see also 11,27,[32][33][34][35][36] ). These data suggested the possibility that the urinary bladder hypersensitivity produced by acute bladder inflammation in the adult rat may be concomitantly suppressed by inflammation-induced activation of an inhibitory system 37,38 and that the enhancement effect we observed with neonatal exposure to zymosan might be due to impairment of this inhibitory system.…”
Section: Introductionmentioning
confidence: 99%
“…Microinjection of selective NMDA receptor antagonists prevented the inflammation-induced increase in RVM excitability. 68 Thus, the enhanced descending modulation appears to be mediated by changes in the activation of the NMDA receptor in the RVM.…”
Section: Function In Chronic Painmentioning
confidence: 99%
“…One possibility is that in females, morphine activates a pain facilitation network. A PAG-RVM pain facilitatory system has been shown to contribute to hyperalgesia produced by opiate withdrawal (Bederson et al, 1990), chronic inflammation (Terayama et al, 2000,Guan et al, 2002, and morphine tolerance ). Interestingly, morphine-induced hyperalgesia is significantly more pronounced in females in comparison to males (Holtman and Wala, 2005).…”
Section: The Pag-rvm Circuit Is Preferentially Activated In Male Ratsmentioning
confidence: 99%